2017
DOI: 10.4067/s0718-95162017005000008
|View full text |Cite
|
Sign up to set email alerts
|

Silicon fertilization reduces the deleterious effects of water deficit in sugarcane

Abstract: Few studies have focused on water deficit for sugarcane, whose damage could be reduced with Si, as shown in other crops. This study aimed to determine whether Si fertilization enhances the best recovery of sugarcane after two periods of the formative phase (tillering and early grand growth) for RB86-7515 (drought tolerant) and RB85-5536 (drought sensitive), and which growth phase is beneficial for each cultivar. It was investigated: 1) the effect of Si fertilization on total Si uptake, and on soluble Si in soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 17 publications
2
37
0
Order By: Relevance
“…Sugarcane is the leading crop for worldwide sugar and bioenergy production (Camargo et al 2017). Apart from economic and social value, sugarcane can be used as a renewable and a clean energy source .…”
Section: Introductionmentioning
confidence: 99%
“…Sugarcane is the leading crop for worldwide sugar and bioenergy production (Camargo et al 2017). Apart from economic and social value, sugarcane can be used as a renewable and a clean energy source .…”
Section: Introductionmentioning
confidence: 99%
“…Previous study has confirmed that silicate fertilization using CaSiO 3 increases sugarcane biomass (Camargo et al, 2017). The Si effects on plant development are related to several ultrastructural, biochemical, and physiological changes.…”
Section: Biomass Yield and Si Accumulation In Shootsmentioning
confidence: 58%
“…Several Si sources varying in total Si contents and solubility are used in Brazil. Most studies use calcium silicate (CaSiO 3 ) and slags (Camargo et al, 2017;Liang et al, 2015), and only a few studies tested diatomites as a Si source to crops (Nascimento et al, 2020). Diatomite is a sedimentary rock formed by the accumulation of diatom algal fossils and composed predominantly of amorphous silica (SiO 2 .nH 2 O) (Sandhya & Prakash, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Water-deficit-tolerant cultivars present greater a stomatal control and photosynthesis rate than those of sensitive genotypes (Graça et al, 2010). In addition, cropping techniques can be associated with irrigation deficit depths to minimize the effect of water deficit (for example, fertilization with silicon) (Camargo et al, 2017).…”
Section: Resultsmentioning
confidence: 99%